The Relationship of workload and muscle flexibility with low back pain among nurses at Moh. Ridwan Meukarsa Level II hospital - Rabillah, Salsa; Siregar, Tatiana (University of Muhammadiyah Malang, 2026)
Introduction: Low back pain (LBP) is one of the most frequently reported musculoskeletal disorders among nurses, commonly associated with repetitive physical demands, non-ergonomic postures, and prolonged standing or bending during patient care. These conditions may reduce functional capacity and interfere with work quality.Objectives: To examine the association between workload and muscle flexibility with the incidence of low back pain among nurses at Moh. Ridwan Meukarsa Level II Hospital.Methods: This study applied a cross-sectional design involving 129 nurses who met the inclusion criteria and were recruited using total sampling. Data were gathered through a workload questionnaire, the Toe Touch Test to assess muscle flexibility, and the Pain and Distress Scale to measure lower back pain. Statistical analysis was performed using chi-square tests and multiple logistic regression to identify the most influential variables. Ethical approval for this research was granted by RS TK. II Moh. Ridwan Meukarsa Jakarta, under letter number Sket/249/VII/2025, issued on July 21, 2025.Results: A substantial number of nurses experienced low back pain. Statistical findings showed a significant association between workload and LBP (p < 0.001), and between muscle flexibility and LBP (p < 0.001). Multivariate analysis confirmed that high workload and reduced flexibility independently contributed to increased LBP risk.Conclusions: Workload and muscle flexibility were significantly associated with the incidence of LBP. Implementing workload regulation strategies, ergonomic improvements, and routine flexibility exercises is recommended to support musculoskeletal health and enhance nursing work performance.